Veljavnost in zanesljivost protokola merjenja moči sukalk ramen na namensko izdelani izometrični upornici - Spudić, Darjan (Šport (Ljubljana), 2021)
The shoulder joint is at high risk of injury in overhead sports. Muscle strength and flexibility deficits or imbalances are one of the main risk factors for acute or overuse injuries. Isometric strength measurements with a hand-held dynamometer provides a simple and applicable method for assessing shoulder rotator strength. However, the reliability of the measurements is questionable. The main objective of our study consisted of two parts: First, to investigate the intra-session reliability of a shoulder internal and external rotation strength obtained with a hand-held dynamometer and a custom-built isometric device, and second, to compare the aforementioned strength variables between the two devices. Good-to-excellent relative (ICC2.1 > 0.805) and acceptable absolute (CV < 6 %) reliability was found for the observed variables, regardless the device used. Moderate-to-large correlations were found between the devices and the standard error of measurement was the largest (4.2 %) in the case of internal rotation contralateral strength ratio. Statistically significantly higher absolute values were obtained with the hand-held dynamometer. The custom-built isometric device proved to be reliable and valid. Sports practitioners should be aware of the discrepancy between devices and attempt to use the same device to longitudinally assess isometric shoulder rotator strength in overhead athletes.
Keywords: concurrent validity; handheld dynamometry; konstruktna veljavnost; measurements; meritve; metalni športi; mišična moč; muscle strenght; navor; overhead sports; ponovljivost; ramenski sklep; reproducibility; ročna dinamometrija; shoulder joint; sport; sports injuries; šport; športne poškodbe; torque